How food cues can enhance and inhibit motivation to obtain and consume food. (1st January 2015) - Colagiuri, Ben; Lovibond, Peter F.
Highlights: Pavlovian-instrumental transfer occurs when tested under instrumental reinforcement. Cues influence motivation to obtain food even when the food is already available. When participants are satiated, food cues increase responding and consumption. When participants are not yet satiated, unpaired cues inhibit responding. Targeting food cues may be useful for preventing over-consumption. Abstract: Learning may play an important role in over-eating. One example is Pavlovian-to-instrumental transfer (PIT), whereby reward cues facilitate responding to obtain that reward. Whilst there is increasing research indicating PIT for food in humans, these studies have exclusively tested PIT under instrumental extinction (i.e. when the food is no longer available), which may reduce their ecological validity. To address this, we conducted two experiments exploring PIT for food in humans when tested under instrumental reinforcement. Participants first underwent Pavlovian discrimination training with an auditory cue paired with a chocolate reward (CS+) and another auditory cue unpaired (CS−). In instrumental training participants learnt to press a button to receive the chocolate reward on a VR10 schedule. In the test phase, each CS was presented whilst participants maintained the opportunity to press the button to receive chocolate. In Experiment 1, the PIT test was implemented after up to 20 min of instrumental training (satiation) whereas in Experiment 2 it was implemented after only 4 min of instrumental training. In both experiments there was evidence for differential PIT, but the pattern differed according to the rate of responding at the time of the PIT test. In low baseline responders the CS+ facilitated both button press responding and consumption, whereas in high baseline responders the CS− suppressed responding. These findings suggest that both excitatory and inhibitory associations may be learnt during PIT training and that the expression of these associations depends on motivation levels at the time the cues are encountered. Particularly concerning is that a food-paired cue can elicit increased motivation to obtain and consume food even when the participant is highly satiated and no longer actively seeking food, as this may be one mechanism by which over-consumption is maintained.